Small-scale irrigation: is this the future? - Facon, T.; Mukherji, Aditi (2010)
The authors were asked to answer the question ?small-scale irrigation: is this the future??. Taking as a starting point the analyses and of the IWMI-FAO-ADB study on Revitalizing Asia?s Irrigation and its key strategies, the paper compares atomistic irrigation, traditional small-scale and large-scale irrigation options, outcomes and potentials in their socio-economic and river basin environments. Atomistic irrigation has exploded, river basins are closing and energy prices are soaring. This new reality, its benefits, its sustainability crisis, but also the potential for new strategies that this phenomenon has demonstrated must first be acknowledged.